2014
DOI: 10.1038/gt.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral transfer of human aquaporin -1 gene to rat liver improves bile flow in estrogen-induced cholestasis

Abstract: Estrogens can cause liver cholestatic disease. As downregulation of hepatocyte canalicular aquaporin-8 (AQP8) water channels has been involved in estrogen-induced bile secretory failure, we tested whether the archetypal water channel AQP1 improves 17α-ethinylestradiol (EE)-induced cholestasis. EE administration to rats reduced bile flow by 50%. A recombinant adenoviral (Ad) vector encoding human AQP1 (hAQP1), AdhAQP1, or a control vector was administered by retrograde bile ductal infusion. Hepatocyte canalicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 29 publications
8
49
0
Order By: Relevance
“…After the procedure was completed, the catheter was gently removed, the duodenal puncture and abdominal wall were sutured, and the animal was allowed to recover. Initial experiments indicated that the protein expression of hAQP1 in hepatocytes takes 72 hours . Thus, the experiments were performed 72 hours after adenoviral infusion (i.e., on the sixth day after starting EE treatment).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the procedure was completed, the catheter was gently removed, the duodenal puncture and abdominal wall were sutured, and the animal was allowed to recover. Initial experiments indicated that the protein expression of hAQP1 in hepatocytes takes 72 hours . Thus, the experiments were performed 72 hours after adenoviral infusion (i.e., on the sixth day after starting EE treatment).…”
Section: Methodsmentioning
confidence: 99%
“…The gene transfer of the archetypal human aquaporin‐1 (hAQP1) water channel through the adenoviral vector encoding hAQP1 (AdhAQP1) has been successfully used to restore normal salivary flow to irradiated hypofunctional salivary glands in experimental animals and humans . We have recently provided evidence suggesting that the adenoviral transfer of hAQP1 gene to livers of EE‐induced cholestatic rats improves bile flow, at least in part by enhancing the canalicular hAQP1‐mediated osmotic water secretion . In an effort to fully understand the mechanisms involved in the hAQP1‐induced improvement of estrogen‐induced cholestasis, we further studied the biliary output of BS and the functional expression of BSEP.…”
mentioning
confidence: 99%
“…(1) We thank the authors for their comments in our recent studies. (2,3) Nevertheless, we believe that an analysis of the role of aquaporins (AQPs) in hepatocyte canalicular water transport and bile secretion should take into account several published contributions that were not cited in the editorial.…”
Section: To the Editormentioning
confidence: 99%
“…Nevertheless, the retrograde biliary vector administration allowed that most of the periportal hepatocytes were transduced with AQP1. (2,3) This is relevant because periportal hepatocytes are exposed to the highest blood concentrations of bile salts and thus are the primary cells involved in bile-salt-dependent bile secretion.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation